EVALUATION OF INTERNAL CONTROL IN THE AUDIT OF LEASING OPERATIONS - Любенко, Андрій; Хомуляк, Тарас (Socio-economic relations in the digital society, 2020)
An article is dedicated to organizational aspects of auditing leasing companies. In particular, researched assessment of internal control audits in the beginning stage of leasing activity. The complex and multifaceted nature of leasing, ambiguous interpretation of its content in the regulatory framework causes difficulties in the verification auditor leasing operations. Frequent changes of laws, high standards of control to leasing companies indicate the need for services of third-party audit professionals. The paper outlines the benefits assessment of internal controls for the proper development of the steps of auditing leasing operations, specific features of its implementation. The internal controls in leasing companies due to a large number of transactions with fixed assets, as objects of lease agreements is needed for conducting audits. The purpose of the research and evaluation of internal control auditor leasing company is to prepare a basis for audit planning and determine of type, amount and timing of audit procedures. Such procedures are recommended, including a number of international auditing standards. To examine the internal control auditor may through surveys, observations, requests to different subjects of inspection, assessing accounting data and the results of previous inspections. We generated list for verification total and partial control that the auditor may use to determine the effectiveness of internal audit. Emphasized the importance of documenting the identified deficiencies to justify the decisions taken on further audit procedures. A question to test internal control system leasing company. The scheme also detailed evaluation of internal audit. The technique of evaluating the effectiveness of internal control of leasing companies allow external auditor to develop an optimal audit program, select the necessary procedures and controls to achieve the proper result.